THE READINESS OF PARENTAL INVOLVEMENT IN TECHNICAL VOCATIONAL EDUCATION AND TRAINING FOR SPECIAL EDUCATION NEEDS: CONFIRMATORY FACTOR ANALYSIS APPROACH (CFA) (Proceedings of International Conference on Special Education, 2015)
Parental involvement in technical and vocational education is vital to enable primary school teachers in carrying out their daily tasks in school. This particular study aims to identify and to validate the conceptual framework of the study and determine the validity and reliability of the instruments used. The instrument used in this study was composed of 25 items that will measure five key constructs defined. Exploratory factor analysis (EFA) and Confirmatory Factor Analysis (CFA) was conducted in this study. Parental involvement in technical and vocational education can be measured through sub-construct parenting, communicating, volunteering, home-learning, decisionmaking, and collaboration with the community. The sample was composed of 453 men and women in some selected primary schools in several areas in Negeri Sembilan. The findings of the CFA analysis found that the model used to measure the readiness of parent involvement in technical and vocational education with the reliability of each sub-construct between 0.78-0.86